EFEKTIVITAS PENERAPAN PEMBELAJARAN MATEMATIKA QUR’ANI DALAM PEMBELAJARAN HIMPUNAN - Gradini, Ega; Wahyuni, Septia; Ansor, Ansor (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Conducting successful mathematics instructions that attach values is a major issue of mathematics education recently. Various programs have been done to meet the purpose. One of them is knowledge islamization which is believed as an alternative-strategic solution. This effort is compatible with the objective of education in Aceh and Indonesia Education System that annunciate the goal of Education in Indonesia to bring the people into religious life. Then, integration of Islamic values onto mathematics instruction is an alternative that has to be chosen in order to make integrated-holistic education. This study aims to determine the effectiveness of the implementation of Qur'anic Mathematics Instruction (QMI) on Set theory. It was a follow-up of QMI Research and Development that has been designed before. Data gathered through test, teacher’s and students’ activity observations. Three madrasah with the indexes of competency are